REPRESENTASI GENDER PADA FILM TILIK MENURUT STUDI SEMIOTIK ROLAND BARTHES - Wijaya, Jonathan Adi; Firmanto, Antonius Denny (Interaksi: Jurnal Ilmu Komunikasi, 2021)
Tilik is a Javanese short film that became a hot topic of conversation after its appearance on the YouTube channel. Tilik emphasizes a certain gender in each scene. As a result, Tilik is seen as perpetuating certain gender stereotypes. The researcher tries to find the meaning behind the gender used as the main character. With wider possibilities for meaning, the researcher also tries to find a deeper meaning that can be found in the Tilik film. Regarding the research objectives, this article poses the following problems: (1) Does Tilik Film perpetuate the stereotype of women? (2) What does the film say about its message? (3) What does the existence of the "truck" say about its function as a container of experience? The object of research is the context of the scenario, images, text, and scenes in the film. This article uses Roland Barthes's qualitative semiotics method. The results of this study indicate that Tilik does not perpetuate gender stereotypes by highlighting a particular gender. On the other hand, Tilik expresses the meaning of social relations in society, struggles in daily life, and the importance of digital literacy as a provision to participate in everyday life by using a certain gender.